Editorial: the dark side of innovation. Issue 1 (2nd January 2021) - Coad, Alex; Nightingale, Paul; Stilgoe, Jack; Vezzani, Antonio
ABSTRACT: We provide a broad discussion of the dark side of innovation, before introducing the papers of the special issue. We start with a critical reply to optimists, complementing the list of indicators showing steady human progress with a list of indicators that show sustained deterioration (largely due to innovation). We then outline some relevant dimensions of harmful innovation, before distinguishing between the types of harm brought on by innovation. We conclude with an overview of the SI papers.